The accuracy of computational fluid dynamics analysis of the passive drag of a male swimmer - Bixler, N.; Pease, D.; Fairhurst, F. (Sports Biomechanics, 2007)
The aim of this study was to build an accurate computer-based model to study the water flow and drag force characteristics around and acting upon the human body while in a submerged streamlined position. Comparisons of total drag force were performed between an actual swimmer, a virtual computational fluid dynamics (CFD) model of the swimmer, and an actual mannequin based on the virtual model. Drag forces were determined for velocities between 1.5 m/s and 2.25 m/s (representative of the velocities demonstrated in elite competition). The drag forces calculated from the virtual model using CFD were found to be within 4% of the experimentally determined values for the mannequin. The mannequin drag was found to be 18% less than the drag of the swimmer at each velocity examined. This study has determined the accuracy of using CFD for the analysis of the hydrodynamics of swimming and has allowed for the improved understanding of the relative contributions of various forms of drag to the total drag force experienced by submerged swimmers.